Developing Sub-wavelength Sound Absorber Based on Coiled Up Tube Resonator - Prasetiyo, Iwan; Wongso, Elsa Nalita; Sarwono, Joko (Journal of Engineering and Technological Sciences, 2019)
Sub-wavelength sound absorbers are attractive for dealing with noise control at low-frequency (long-wavelength) sounds. To be efficient in absorbing the sound energy, resonator based absorbers are preferable over fibrous porous ones. In this paper, a coiling up space approach is introduced to a tube resonator system in order to realize a sub-wavelength absorber structure. In this way, the air channel of the tube resonator is a coplanar coiled up channel rather than a straight channel as found in conventional tube resonators. The effect of the geometrical properties of the aperture and the air channel were studied further to look at their relationship to impedance mismatch, which coiling up systems typically suffer from. It was found that the proposed approach could realize a sub-wavelength absorber system up to 1/32 wavelength of peak sound absorption. Selection of the shape and dimensions of the aperture must be done with great care as indicated by the measurement results. Moreover, the behavior of the coiled up tube resonator deviates from that of the straight tube as the reflection factor is increased, although the target resonance frequency is close to the target. It was also found that a squared aperture shape as well as increasing the cavity thickness is useful to deal with impedance mismatch.